Weather Research and Forecasting Model (WRF) cloud resolving model output, links to NetCDF files - Adrian Mark Tompkins; Addisu G Semie (PANGAEA, 2017)
Radiative-convective equilibrium simulations with a 2 km horizontal resolution are conducted to investigate the impact on convective organization of different parameterizations for horizonal and vertical sub-grid turbulence mixing. Three standard approaches for representing horizontal diffusion produce starkly differing mixing rates, particularly for the entrainment mixing into updrafts, which differ by more than an order of magnitude between the schemes. The simulations demonstrate that the horizontal sub-grid mixing of water vapor is key, with high mixing rates a necessary condition for organization of convection to occur, since entrainment of dry air into updrafts suppresses convection. It is argued that diabatic budgets, while demonstrating the role of spatially heterogeneous radiative heating rates in driving organization, can overlook the role of physical processes such as updraft entrainment. These results may partially explain previous studies that showed that organization is more likely to occur at coarser resolutions, when entrainment is solely represented by subgrid-scale turbulence schemes, highlighting the need for benchmark simulations of higher horizontal resolution. The recommendation is for the use of larger ensembles to ensure robustness of conclusions to subgrid-scale parameterization assumptions when numerically investigating convective organization, possibly through a coordinated community model intercomparison effort.
Supplement to: Tompkins, AM; Semie, AG (2017): Organization of tropical convection in low vertical wind shears: role of updraft entrainment. Journal of Advances in Modeling Earth Systems, https://doi.org/10.1002/2016MS000802